The rise of the partisan nurse and the challenge of moving beyond an impasse in the (re)organization of Dutch nursing work. Issue 1 (9th February 2022) - Felder, Martijn; Kuijper, Syb; Lalleman, Pieterbas; Bal, Roland; Wallenburg, Iris
Abstract: In this article, we reconstruct a Dutch case in which policymakers, experts, and professional organizations proposed to amend a law so as to differentiate between different kinds of nurses and the work they do. In doing so, they specifically sought to support and reposition higher educated nurses. The amendment was met with fierce opposition from within the nursing community, however, and was eventually withdrawn. Drawing on interviews with key actors in the debate and an analysis of policy documents and social media platforms, we reconstruct what happened and how. Our reconstruction is informed by institutional theory, the sociology of professions, and a body of literature that examines populism in its increasingly diverse modes of existence. By combining these bodies of literature, we have sought to expand on an analytical repertoire aimed at capturing the dynamics between individual professionals and their institutional environments. Our approach specifically allowed us to foreground a populist action frame through which opposition was organized and to discuss the destructive and generative potential it has had for future aspirations in the professionalization and (re)organization of nursing work.